Всё вторит весело громам: [стихи : для младшего школьного возраста] / Ф. Тютчев ; рисунки Н. Устинова - Тютчев Федор Иванович (Малыш, 1978)
Экземпляры: РК (20250220) / Инвентарный номер: 1131425 / Сис.шифр: 84(2) / Авт.знак: Т 98 / ГРНТИ: 17 / ББК: 84(2=411.2)-5